Evaluation of anxiety sensitivity in patients with psoriasis - Hilal Kaya Erdogan; Ali Ercan Altinoz; Ersoy Acer; Zeynep Nurhan Saracoglu; Muzaffer Bilgin (Dermatologica Sinica, 2019)
Background/Objectives: Psoriasis is an inflammatory skin disease characterized by erythematous squamous plaques. It has negative physical, psychological, and social effects. Psychiatric comorbidities such as anxiety and depression can accompany to psoriasis. In our study, we aimed to evaluate the anxiety sensitivity (AS) in psoriasis patients. Methods: We included 89 psoriasis patients, 44 controls with nonpsychodermatological disease and 59 healthy volunteers to study. Dermatological examinations were performed, and the Psoriasis Area and Severity Index (PASI) values were calculated. Participants completed a sociodemographic information form, Beck Anxiety Inventory and AS Index-3. Results: Both the psoriasis group and the control group with nonpsychodermatological disease had higher anxiety scores than the healthy control group. Psoriasis patients were found to have higher AS scores than both control group with nonpsychodermatological disease and healthy controls. When the psoriasis group was divided into two groups according to the presence of systemic disease or psoriatic arthritis; there was no difference between the groups in terms of psychometric measurements. Furthermore, there was no significant correlation between PASI scores and disease duration and psychometric evaluations. Conclusion: Our study is the first to show that the AS of psoriasis patients is significantly higher than healthy controls and of those with nonpsychodermatological diseases. It is not clear that high AS in these patients is a predisposing factor to the disease or a consequence of the disease.